2013
DOI: 10.5546/aap.2013.eng.37
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in children and adolescents undergoing surgery of Hirschsprung disease and anorectal malformations

Abstract: Purpose. The objective was to describe health related quality of life (HRQoL) after surgery for Hirschsprung's disease (HD) and anorectal malformations (ARMs) in children according to their own perception and that of their parents, by different age groups, the presence of functional disorders, and diet indication. Methods. This is a cross-sectional descriptive study. Participants were patients aged 2-18 years old and their parents. The study was conducted from June 2008 to May 2009. The instrument used was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These paradoxical results may be explained by more robust psychological coping strategies that patients with chronic illness sometimes display compared with children who have normal health. 28 In accordance with this, the series by Hartman et al 53 found that adolescents with HD and ARM without a cloaca reported better scores in social acceptance, athletic competencies, physical appearance, and global self-worth than in the reference group.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…These paradoxical results may be explained by more robust psychological coping strategies that patients with chronic illness sometimes display compared with children who have normal health. 28 In accordance with this, the series by Hartman et al 53 found that adolescents with HD and ARM without a cloaca reported better scores in social acceptance, athletic competencies, physical appearance, and global self-worth than in the reference group.…”
Section: Discussionmentioning
confidence: 53%
“…[3][4][5][6][7][8][9][23][24][25] However, it has been suggested that bowel mobilization and dissection through the anus has the potential to interfere with anal sphincter integrity and rectal sensation, 3,6,8 but controlled studies of the long-term outcomes after TEPT are lacking. It has also been established that significant impairment of fecal control negatively impacts on quality of life (QoL) and social problems, [26][27][28] and validated assessment of the long-term QoL among HD patients after TEPT is timely. As minor imperfections in fecal control also occur in the general population, 29 controlled series are particularly important in order to delineate how any functional impairment in patients departs from the prevalence observed in matched controls.…”
mentioning
confidence: 99%
“…Recently, attempts have been made to understand the impact of FI in pediatric populations. The majority of the available literature is focused on organic conditions that have FI as one of the associated symptoms (9)(10)(11)(12)(13)(14) rather than focusing on the impact of FI regardless of the associated disease process. Moreover, the majority of the available literature on the topic focuses on children between the ages 7 and 11 (9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…The majority of the available literature is focused on organic conditions that have FI as one of the associated symptoms (9)(10)(11)(12)(13)(14) rather than focusing on the impact of FI regardless of the associated disease process. Moreover, the majority of the available literature on the topic focuses on children between the ages 7 and 11 (9)(10)(11)(12)(13)(14)(15). One of the most instructive studies reporting on the impact of FI beyond the impact of a larger medical condition revealed that, in fact, parents of adolescents with constipation and FI reported worse quality of life (QOL) than parents of children with constipation alone (16),…”
mentioning
confidence: 99%